Ecological integrity is both real and valuable. Issue 2 (19th November 2021) - Karr, James R.; Larson, Eric R.; Chu, Ellen W.
Abstract: Ecological integrity has been criticized as a "bad fit as a value" for conservation biology and restoration ecology. But work over the past four decades centered on ecological integrity—especially biological integrity—has given rise to effective methods for biological monitoring and assessment to better understand the disintegration of living systems, including under scenarios of rapid climate change. Revealing when and where living systems have been altered by human activity, such methods have been adapted and applied most comprehensively in streams and rivers, but also in other ecosystems, ranging from tropical forests to marine coral reefs and on all continents except Antarctica. Equally important, restoration and maintenance of biological integrity is already a fundamental goal in law and offers an inspiring framework for communication and engagement—among scientists, resource managers, law‐ and policymakers, and the public. This essay builds the case that ecological integrity has proved both real and valuable as a conservation paradigm. Abstract : Biological monitoring and assessment founded on the concept of ecological integrity, especially biological integrity, has led to real‐world achievements under the US Clean Water Act. Between 1979 and 2017, for example, the health of Ohio's Scioto River improved so much that as many as 70 fish species, including some that had been absent for more than a century, could again be found in the mainstem river near Columbus. This example is only one of the many demonstrating that ecological integrity is both real and valuable in conservation.